Two jokers that bedevil science - Azram, Mohammad (2015)
Zero was a brilliant innovation and most significant achievement but it has threatened the foundations of modern physics and is behind all of the big puzzles in physics. Today, zero lies at the heart of one of the biggest scientific controversies of all time. The mysterious zero is posing challenges not only to intellectuals, philosophers, scientists, mathematicians, historians and theologizes but also is confusing and un-easing a common man. To have a clear picture of many issues related to mysterious zero, we need to understand clearly about the concept of infinity, which within itself is another mystery. A proper understanding about infinity rests on a careful definition of what is finite? Otherwise we will be facing un-easing and confusing results. This article is devoted to raise awareness of social, conceptual and operational issues related with mysterious zero and infinity. The focus is those individuals involved in the process of applying, teaching and learning mathematics. It is suspected that this article will enable them to think more clearly rather than to be in a state of confusion.